"Torsade de pointes" tachycardia. Re-entry or focal activity?. Issue 3 (September 1982) - D'Alnoncourt, C N; Zierhut, W; Blüderitz, B
Abstract : Paroxysms of ventricular tachycardia in which the amplitude and the direction of QRS complexes change periodically are defined as "torsade de pointes" tachycardias. The mechanism of this atypical ventricular arrhythmia has not yet been elucidated. The aim of our study was to induce "torsade de pointes" tachycardia experimentally, in order to gain insight into its possible mechanism. The experiments were carried out with isolated porcine hearts, perfused by the Langendorff technique. Epicardial electrocardiograms were recorded by unipolar leads. The specific pattern of "torsade de pointes" tachycardia could be induced by stimulation of the right and left ventricles in phase. From our experimental observations we conclude that a possible cause of "torsade de pointes" tachycardia is the interaction of two ectopic ventricular foci.